2017
DOI: 10.7150/jca.19290
|View full text |Cite
|
Sign up to set email alerts
|

Gambogenic Acid Exerts Antitumor Activity in Hypoxic Multiple Myeloma Cells by Regulation of miR-21

et al.

Abstract: Hypoxia is an inseparable component of the bone marrow (BM) microenvironment, accounting for aggressive tumor behavior and poor prognosis of multiple myeloma (MM). Gambogenic acid (GNA) has proven to be an attractive option for treatment of tumors due to its tumor suppressive activity. Herein, we found that GNA exhibits remarkable apoptotic activity against MM cells even under hypoxia. MicroRNA-21 (miR-21) has been found over-expressed in MM patients and associated with the occurrence and development of MM. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
(37 reference statements)
1
11
0
Order By: Relevance
“…Tumor hypoxia is closely related to chemotherapy resistance, and HIF-1α induces expressions of multidrug resistance 1 ( MDR1 ) and multidrug resistance associated protein 1 ( MRP 1 ) genes [ 35 ]. Thus, using selective inhibitors targeting hypoxic cancer cells and HIF-1α is an attractive strategy for development of anticancer agents [ 36 ], and several reports have shown improved efficacy of anticancer drugs by suppressing HIF-1α under hypoxic condition [ 37 ]. Our results additionally revealed that TQ is sufficient to selectively kill hypoxic renal cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Tumor hypoxia is closely related to chemotherapy resistance, and HIF-1α induces expressions of multidrug resistance 1 ( MDR1 ) and multidrug resistance associated protein 1 ( MRP 1 ) genes [ 35 ]. Thus, using selective inhibitors targeting hypoxic cancer cells and HIF-1α is an attractive strategy for development of anticancer agents [ 36 ], and several reports have shown improved efficacy of anticancer drugs by suppressing HIF-1α under hypoxic condition [ 37 ]. Our results additionally revealed that TQ is sufficient to selectively kill hypoxic renal cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…GBA resembles GB but has a geranyl and a hydroxyl group instead of the ether ring in GB (Asano et al 1996). GBA, like GB, is toxic to many different cancer cell lines (Huang et al 2019;Liu et al 2017;Zhou et al 2013). Whether GBA induces a HSR has not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…GBA resembles GB but has a geranyl and a hydroxyl group instead of the ether ring in GB (Asano et al 1996). GBA, like GB, is toxic to many different cancer cell lines (Huang, T. et al 2019; Liu et al 2017; Shen et al 2020; Zhou et al 2013). Whether GBA induces a HSR has not been studied before.…”
Section: Introductionmentioning
confidence: 99%